NEO-INDUSTRIALIZATION OF FORMER INDUSTRIAL REGIONS OF RUSSIA (THE CASE OF “TITANIUM VALLEY”) - Anatoly V. STEPANOV; Maria Y. ILYUSHKINA (European Journal of Geography)
Complex transformational processes in the Russian economy in the ХХ century, which exited a 70-year long experience of a planned-administrative economic system and transitioned to the market model, have led to unprecedented experimentation with the world economy. Having introduced the principles of a market economy, Russia has found itself subjected to the twin pressures of globalization and neo-industrialization, the results of which have proven to be very effective for its industrial structure. Globalization has expanded state borders and opened the gates for Russian entrepreneurs to conquer the world oil and gas markets, ferrous and non-ferrous metals sectors, engineering and chemical industries. The Urals region of Russia is developing in a very intensive way. The “Titanium Valley” production cluster was formed in this region. This article examines some of the special features of the functioning of this cluster.